2018
DOI: 10.1098/rsos.171387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to bodies of different sizes on perception of and satisfaction with own body size: two randomized studies

Abstract: Body dissatisfaction is prevalent among women and associated with subsequent obesity and eating disorders. Exposure to images of bodies of different sizes has been suggested to change the perception of ‘normal’ body size in others. We tested whether exposure to different-sized (otherwise identical) bodies changes perception of own and others' body size, satisfaction with body size and amount of chocolate consumed. In Study 1, 90 18–25-year-old women with normal BMI were randomized into one of three groups to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…In terms of satisfaction with own body size, we also found different results from our previous study [19]. We found no differences in VAS-or questionnaire-rated satisfaction with body size.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In terms of satisfaction with own body size, we also found different results from our previous study [19]. We found no differences in VAS-or questionnaire-rated satisfaction with body size.…”
Section: Discussioncontrasting
confidence: 95%
“…Limitations of these previous studies include small sample size [16][17][18], and images lacking in ecological validity since they were uniformly modified to appear of different sizes rather than manipulated in line with typical patterns of weight gain [19]. Further possible limitations of previous studies are their reliance on measures that are susceptible to bias due to demand characteristics: that is, participants inferring the aim of a study and trying to be 'good subjects' by attempting to respond in the way they believe will assist the researchers [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015 and 2005, boys in the normal weight range became more likely to think they were overweight compared with 1986, whereas girls became more likely to think their weight was about right when underweight in 2015 compared with 1986 and 2005. Greater public health focus on calorie restriction and exercise, [43][44][45][46] the proliferation of the fitness industry, 47 and growing societal and media portrayals of lean female and male bodies 48-52 could have led to adolescents' increasingly internalizing thin body ideals 53 and weight stigma, which are known correlates and predictors of restrictive eating behaviors, poor self-esteem, and depression. 54,55 A recent systematic review on young people's view on body image and weight in the UK found that children with higher BMIs report appearance-based bullying resulting in social iso-lation and low mood 56 and that young people think it is a person's responsibility to maintain a healthy weight-an idea often reinforced by media 57 -leading to high levels of selfblame for failing to lose weight.…”
Section: Boymentioning
confidence: 99%
“…Clearly, media can shape our beliefs and attitudes, but can exposure to certain body types change the way we actually perceive our own bodies? Recently, several studies suggested that this might be the case and proposed visual adaptation, i.e., a shift in perceptual judgment after prolonged exposure to a certain stimulus, as one of the mechanisms that may be involved in this process (Hummel et al, 2012b; Brooks et al, 2016; Bould et al, 2018; Stephen et al, 2018). According to this emerging theory, exposure to idealized, often extremely thin bodies (e.g., “size zero” models) causes our own body to be perceived as fatter than it really is.…”
Section: Introductionmentioning
confidence: 99%